1994
DOI: 10.1038/scientificamerican1194-48
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Reproducing Inflationary Universe

Abstract: According to the inflationary universe scenario the universe in the very early stages of its evolution was exponentially expanding in the unstable vacuum-like state. At the end of the exponential expansion (inflation) the energy of the unstable vacuum (of a classical scalar field) transforms into the energy of hot dense matter, and the subsequent evolution of the universe is described by the usual hot universe theory.Recently it was realised that the exponential expansion during the very early stages of evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(54 citation statements)
references
References 61 publications
0
53
0
1
Order By: Relevance
“…The hypothesis advanced in [1] was an attempt to extend and refine Lee Smolin's conjecture [3] that the majority of the anthropic qualities of the universe can be explained as incidental consequences of a process of cosmological replication and natural selection (CNS) whose utility function is black hole maximization. Smolin's conjecture differs crucially from the concept of eternal chaotic inflation advanced by Andrei Linde [4] in that it predicts a cosmological evolutionary process with a specific and discernible utility function-black hole maximization. It is this aspect of Smolin's conjecture rather than the specific utility function he advocates that renders his theoretical approach genuinely novel.…”
Section: Introductionmentioning
confidence: 95%
“…The hypothesis advanced in [1] was an attempt to extend and refine Lee Smolin's conjecture [3] that the majority of the anthropic qualities of the universe can be explained as incidental consequences of a process of cosmological replication and natural selection (CNS) whose utility function is black hole maximization. Smolin's conjecture differs crucially from the concept of eternal chaotic inflation advanced by Andrei Linde [4] in that it predicts a cosmological evolutionary process with a specific and discernible utility function-black hole maximization. It is this aspect of Smolin's conjecture rather than the specific utility function he advocates that renders his theoretical approach genuinely novel.…”
Section: Introductionmentioning
confidence: 95%
“…) The second alternative is that the universe in which we reside is but one of infinitely many universes and that within the whole infinite set, everything mathematically possible somewhere becomes a physical reality, as conjectured by the physicist Max Tegmark (1998). If universes endlessly spawn other universes, perhaps in one of the ways envisioned by Andrei Linde (1994), Lee Smolin (1997), or Tegmark, symmetry may be broken differently in the birth ofeach new universe, yielding different laws of physics (perhaps corresponding to such symmetry groups as SU (5), SU(4) X U(1), or SU(3) X SU(2) X D(1), as Linde suggested). Only in a tiny fraction of these universes would the resulting laws of physics be compatible with the emergence of life and, hence, of mind.…”
Section: Keynote Address 19mentioning
confidence: 99%
“…Smolin (1997) has suggested that the physical properties have evolved via natural selection as universes continually give birth to new universes during black hole formations. Similarly, Linde (1994) has proposed that universes are continually sprouting new and different universes via the Guth inflationary process that is believed to have occurred during the big bang.…”
Section: Definition Of a Toementioning
confidence: 99%